The logic of pronominal resumption - Asudeh, Ash. (Oxford : Oxford University Press, 2012)
This title is a cross-linguistic investigation of resumptive pronouns and related resumption phenomena. The author proposes a new theory of resumption based on the use of a resource logic for semantic composition and the observation that resumptive pronouns are ordinary pronouns in their morphological and lexical properties.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Grammar, Comparative and general -- Pronoun; Grammar, Comparative and general -- Relative clauses